(untitled) (INNOTEC, 2019)
Selenium (Se) levels in different foods is variable depending on its natural availability. Beef is considered a good source of this trace element for human nutrition. The variation of Se levels in three cuts of beef and in different cooking points was studied. The selected cuts were rib plate, rump and knuckle and were analyzed in 20 animals. Each sample was divided into several portions and cooked in a cooking plate and oven. Analytical determinations were made from previously dried and ground meat. Microwave assisted digestion and subsequent selenium determination was performed by atomic emission spectrometry with microwave-induced plasma coupled to hydride generation (HG-MIP OES). The cooking points were established by evaluating the weight loss (from 8 to 35%). The results indicate that beef provides between 20 and 26% of the daily intake requirement of Se of an adult. It was observed that this percentage remains without significant changes even after a weight loss of up to 35%, thus concluding that cooking does not influence the contribution to the diet of this trace element.